Knowledge and Attitudes of Seniors about Diabetes Mellitus - Mezher , Mohammed K.; Hussain, Ala’a Hassan Mirza (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To evaluate the knowledge and attitude towards diabetes and their association with age, marital status, education level, and monthly income among seniors with diabetes mellitus.Methods: A cross- sectional descriptive study was carried out among 69 seniors with diabetes mellitus who were attending the Center for Endocrinology and Diabetes in AL-Muthanna Governorate. Data were collected using two scales; one for knowledge (DKN) and the other for attitudes through self-reporting. Data were analysed using IBM-SPSS. Results: The study indicated that the knowledge of senior patients was very poor in all items of the DKN scale and, only 6 (8.7%) had acceptable knowledge, while 63 (91.3%) of them lack information about diabetes mellitus type2. As well as, their attitude was negative in most items of attitude scale, with a mean total of 2.43 ± 0.584. In addition, there is a statistically significant association between patients’ knowledge and monthly income at the level of 0.05.Conclusion: The seniors had a poor knowledge with negative attitudes toward diabetes.Recommendations: Significant efforts are required to enhance seniors' understanding and attitudes toward effectively managing their health and illnesses